TO BE SEEN. : Queer Lives 1900-1950 - Kühn, Karolina; Zadoff, Mirjam (München : Hirmer, 2023)
Authors : Gogtas, Gürsoy ; Dudley, Michaela ; Gilman, Sander L. ; Herzog, Dagmar ; Klöppel, Ulrike ; Miller, Ben ; Schweitzer, Cara ; Tremblay, Sébastien ; Zadoff, Mirjam
The contributions that have been assembled in this volume present the story of queer lives – from the first emancipation movements around the turn of the (last) century via attempts at self-empowerment in the Weimar Republic to the destruction of queer subcultures under the National Socialist regime and the continued discrimination of LGBTIQ+ persons in the postwar period. Since the late 19th century, increasing numbers of people have self-assuredly championed the recognition of queer lifestyles. These pioneers formed collectives, made their voices heard and questioned dominant gender categories politically, scientifically and artistically. Through essays, interviews and artworks the authors and artists illustrate this struggle for recognition which was forcefully prevented and destroyed following the seizure of power by the National Socialists and almost forgotten after 1945.(from publisher)
TO BE SEEN. Queer Lives 1900-1950, NS-Dokumentationszentrum, München, 7.10.2022 - 21.05.2023
boek